2006
DOI: 10.1111/j.1439-0507.2006.01199.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophytoses in Monterrey, México

Abstract: In the present report we reviewed a total of 2397 cases of dermatophytosis from superficial cutaneous lesions between the years 1978 and 1990. The cases included were from the Department of Dermatology at the University Hospital located in the city of Monterrey, México. A total of 726 tinea pedis, 613 tinea unguium, 441 tinea capitis, 395 tinea corporis and 222 tinea cruris cases were observed. The most commonly isolated dermatophyte species was Trichophyton rubrum (45%), followed by Trichophyton mentagrophyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
33
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 13 publications
8
33
0
2
Order By: Relevance
“…Correlating the species with the anatomical localisation revealed that T. tonsurans was the most frequent isolate in scalp lesions (73.9%), whereas T. rubrum was the main species involved in body lesions (72.8%).Mexico. Welsh et al have published data fromMonterrey involving 2397 cases of dermatophytosis from superficial cutaneous lesions between 1978 and 1990 69. Seven hundred and twenty-six (30.2%) cases of tinea pedis, 613 (25.6%) of tinea unguium, 441 (18.4%) of tinea capitis, 395 (16.4%) of tinea corporis and 222 (9.3%) of tinea cruris were observed.…”
mentioning
confidence: 85%
“…Correlating the species with the anatomical localisation revealed that T. tonsurans was the most frequent isolate in scalp lesions (73.9%), whereas T. rubrum was the main species involved in body lesions (72.8%).Mexico. Welsh et al have published data fromMonterrey involving 2397 cases of dermatophytosis from superficial cutaneous lesions between 1978 and 1990 69. Seven hundred and twenty-six (30.2%) cases of tinea pedis, 613 (25.6%) of tinea unguium, 441 (18.4%) of tinea capitis, 395 (16.4%) of tinea corporis and 222 (9.3%) of tinea cruris were observed.…”
mentioning
confidence: 85%
“…27 Existe uma predominância de T. rubrum como principal agente etiológico em várias regiões geográ-ficas do mundo, como Japão, Estados Unidos, México e Brasil. 28 No entanto, alguns estudos mostram o aparecimento de outros dermatófitos como principais agentes causadores de infecção, entre eles o T. mentagrophytes e o M. canis. 29,30 A efetividade do tratamento tópico de infecções fúngicas continua sendo um importante desafio em dermatologia.…”
Section: Resultsunclassified
“…Our study showed that in most of the tinea cases the male: female ratio was quite similar, except for Tinea pedis (Female > males) and in tinea versicolor (Males > females). Welsh et al [16] reported that most of the cases were equally distributed in both genders, except for Tinea cruris which was more prevalent in men (3.5: 1 ratio). In the present study, the clinical diagnosis of 53 patients showed that 26.6% of patients were suffering from T.corporis followed by 22.6% with both T.pedis and T.versicolor, 18.9% of patients with T.cruris and Tinea capitis in only (9.4%).…”
Section: Discussionmentioning
confidence: 99%